The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1532-5415.2007.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Cerebral Infarction in Alzheimer's Disease Is Associated with Fast Dementia Progression: Applying the National Institute for Neurological Disorders and Stroke/Association Internationale pour la Recherche et l'Enseignement en Neurosciences Neuroimaging Criteria in Alzheimer's Disease with Concomitant Cerebral Infarction

Abstract: In AD, co-occurrence of CI with distribution and severity as defined in the NINDS-AIREN neuroimaging criteria for VaD is associated with faster dementia progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…1 Although some studies suggested that in patients with clinical Alzheimer's disease (AD), comorbid cerebrovascular disease was associated with a more rapid cognitive decline, 2,3 it is still unknown whether concurrent presence of Alzheimer's pathology is associated with a faster cognitive deterioration in patients with poststroke/TIA cognitive impairment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Although some studies suggested that in patients with clinical Alzheimer's disease (AD), comorbid cerebrovascular disease was associated with a more rapid cognitive decline, 2,3 it is still unknown whether concurrent presence of Alzheimer's pathology is associated with a faster cognitive deterioration in patients with poststroke/TIA cognitive impairment.…”
mentioning
confidence: 99%
“…Our recent in vivo study using carbon-11-labeled Pittsburgh compound B ( 11 C-PiB) positron emission tomography (PET) found that ≈30% of subjects with poststroke/TIA cognitive impairment harbored Alzheimer's pathology. 1 Although some studies suggested that in patients with clinical Alzheimer's disease (AD), comorbid cerebrovascular disease was associated with a more rapid cognitive decline, 2,3 it is still unknown whether concurrent presence of Alzheimer's pathology is associated with a faster cognitive deterioration in patients with poststroke/TIA cognitive impairment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Song et al (44) observed that AD with silent cerebral infarction showed a more severe cognitive decline than AD without vascular disease, indicating that cerebrovascular disease contributes to the severity of cognitive decline. Also, Sheng et al (45) showed that AD with coexisting cerebral infarction (satisfying criteria for VaD) was associated with faster progression of dementia. These findings suggest that prevention of cerebrovascular disease may play an important role in preventing the rapid cognitive decline of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Current investigations have demonstrated a close link between sporadic Alzheimer's disease and ischemic brain episodes [6,43,44,47,50,53,63]. Additionally, earlier epidemiological studies noted that brain is chemia increased the incidence of sporadic Alzheimer's disease [15] and neurovascular risk factors for brain is chemia also raised the risk of sporadic Alzheimer's disease [58].…”
Section: Introductionmentioning
confidence: 99%